BANGKA MBULE-MBULE TRADITION AS A CULTURAL TOURIST ATTRACTION IN WAKATOBI, SOUTH EAST SULAWESI - Yusuf, La Ode; Cika, I Wayan; Arsana, I Gusti Ketut Gde (E-Journal of Cultural Studies; Volume 10, Number 3, August 2017, 2017)
Globalization has caused tradition to change, meaning that globalization has caused the sacred tradition to change into the propane tradition as it has been used as a tourist attraction. This present study discusses the Bangka mbule-mbule tradition used as a tourist attraction in Wakatobi Regency, South East Sulawesi. The study is intended to inform the public that the Bangka mbule-mbule has been performed as a cultural tourist destination. The study uses the descriptive qualitative method. The data which were obtained from the field were qualitatively described. The social theory combined with the theory of cultural tourism department was used to analyze the data. The result of the study shows that Tradition can be defined as a right heritage or a heritage from the past which is still currently found in society. One of the traditions which is still performed is the bangka mbule-mbule tradition. It is still performed by Mandati people in Wakatobi Regency, South East Sulawesi. The owners of the tradition still believe in it. It has been performed to support the cultural tradition in Wakatobi. The implication is that it has increased the number of tourists visiting Wakatobi, South East Sulawesi.